An Obstacle Detection and Avoidance of A Mobile Robot with Stereo Vision Camera - Hamzah, Rostam Affendi (2011)
This paper presents an obstacle detection and avoidance of mobile robot using stereo camera for indoor environment. Block matching algorithm is solved the correspondence problem occurred in comparing stereo images (left and right sensors of the camera).